Husband involvement in postnatal care services utilization and associated factors in Bishoftu Town, Central Ethiopia; community-based cross-sectional study - Gesisa, Hana Israel; Oyato, Befekadu Tesfaye; Sileshi, Warkitu; Abasimel, Husen Zakir; Hussien, Dursa (Frontiers in Global Women's Health, 2024)
BackgroundBoth mothers and newborns go through a critical time in their lives during the postnatal period, and the majority of deaths of mothers and neonates happen during this period. Postnatal care is the care given to women and their neonates, starting from delivery to 42 postnatal days. Although the significance of postnatal care in maternal and child health is acknowledged, the influence of husbands in either facilitating or impeding access to these services has been largely unexplored. So it's important to find out husbands’ involvement in postnatal care service utilization in Bishoftu town.ObjectivesTo assess husband involvement in postnatal care services utilization and associated factors in Bishoftu town, Central Ethiopia.MethodsA community-based cross-sectional study was conducted in Bishoftu town, central Ethiopia, between April 1 and 27, 2022, among 624 fathers. After being selected through simple random sampling, 610 husbands were interviewed face-to-face. The data was then entered into Epi-Data version 3.1 and analyzed using SPSS version 26. Binary logistic regression was employed for analysis and variables with a p-value ≤0.2 in the bivariate analysis were entered into multivariable logistic regression analysis. In multivariable analysis, statistical significance was declared at p-value <0.05.ResultsThis study reveals that overall husband involvement in postnatal care utilization was found to be 34.1% with a 95% CI (30.3%–38.0%). Residing in urban areas (AOR = 2.3, 95% CI 1.39–3.82), having good knowledge of neonatal (AOR = 3.1, 95% CI 2.04–4.7) and maternal danger signs and complications during the postnatal period (AOR = 2.44; 95% CI: 1.64, 3.63), having history of child illness (AOR = 2.18; 95% CI: 1.4–3.3), and accompanying wife in antenatal care services (AOR = 2.73, 95% CI 1.82–4.07) were the factors found to determine husband's involvement in postnatal care service utilization.ConclusionThe level of husband involvement in their spouse's postnatal care service utilization was relatively low in this study. Encouraging husbands to participate in prenatal care services, availing healthcare facilities to rural communities, and increasing community awareness of maternal and neonatal warning signs might boost husbands’ involvement in postnatal care services utilization.